Use of RFLPs and RAPDs in cassava genomic studies - Angel, F.; Giraldo, F.; Gómez, R.; Iglesias, C.A.; Tohme, Joseph M.; Roca, W. (International Center for Tropical Agriculture, 1993)
The construction of a detailed genetic map of cassava (Manihot esculenta Crantz) will be useful to tag agronomically important trais as well as to isolate and to clone cassava genes in the future. This map will also contribute to the understanding of cassava genomic structure and evolution. As a first step in developing the cassava molecular map, cloned nuclear sequences and several oligodeoxy-nucleotides primers were used to study different crosses in Manihot. Polymorphisms and segregations were detected in the parental lines and their offspring, respectively. Cloned nuclear sequences and different primers used, each 10 nucleotides in length, were selected previously on the basis of their ability to detect polymorphism in the parental lines (Angel et al., 1991). An interspecific cross (MCol 1505 x M. aesculifolia) and an intraspecific cross (MCol 1522 x CM2772-3) were evaluated by both RFLPs and RAPDs. Segregation of the markers used here in the two crosses will be presented and discussed.$$bSumario (spa)